Digital Economy Post COVID-19 Era Proceedings of 8th Conference of Indian Academy of Management (INDAM2023), Mumbai, India 2023 - Mishra, Prashant; Sharma, Ashu.; Khanra, Sayantan; Kundu, Sumit K.; Mishra, Sushanta Kumar (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book presents the future directions of the digital economy post Covid-19 era. The chapters of this book cover contemporary topics on digital economy and digital initiatives undertaken by various organizations. Overall, the book shares insights on how organizations can adapt and transform their processes, structure, and strategies to remain relevant and competitive in the new business and economic environment. These insights also emerge from multidisciplinary discussions in various management domains, such as, consumer behaviour and marketing, economics, finance and accounting, entrepreneurship and small business management, environmental, social and governance compliance, future of work, human resource management, leadership, inclusive workforce, information systems and decision sciences, international business and strategy, and operations and supply chain management.
Digital Economy Post COVID-19 Era -- Case Studies on Conference Theme -- Consumer Behaviour and Marketing -- Contemporary Topics -- Economics, Finance and Accounting -- Entrepreneurship and Small Business Management -- Environmental, Social, and Governance Compliance -- Future of Work -- Human Resource Management -- Inclusive Workplaces -- Information Systems and Decision Sciences -- International Business and Strategy -- Leadership -- Operations and Supply Chain Management.
Keywords: Technological innovations; Business information services; Electronic commerce; Information technology -- Management; Strategic planning; Leadership; Economic policy; Innovation and Technology Management; IT in Business; E-Business.; Business IT Infrastructure; Business Strategy and Leadership; Economic Policy